Why is Unemployment so High At Full Capacity? : The Persistence of Unemployment, the Natural Rate, and Potential Output in the Federal Republic of Germany - Krueger, Thomas (IMF Working Papers; Working Paper, 1990)
The empirical analysis indicates that in the Federal Republic the unemployed primarily influence the relationship between the level of real wages and productivity, rather than the growth of wages. This result suggests a distinction between an equilibrium natural rate of unemployment, which is estimated to have been 3-4 percent in the 1980s, and a quasi-equilibrium unemployment rate closer to actual rates of 7-8 percent. Corresponding to these two concepts of equilibrium unemployment, estimates are presented of alternative concepts of potential output that differ according to whether labor input is consistent with the quasi-equilibrium rate of unemployment or with the natural rate of unemployment.